(untitled) (Религиски дијалог и соработка, 2020)
This paper aims to analyze an example of how intrareligious dialogue and peaceful coexistence are dealt with in the Arabic novel. It focuses on two works by Jordanian writer Ġālib Halasā, namely the short story Wadīʿ wa-al-qaddīsa Mīlāda waaḫarūn (1968) and the novel Sulṭāna (1989). The purpose of the paper is to show how such a cohabitation is portrayed by the author, coupling a historical and a literary reading, in order to show some sides of peaceful coexistence in Jordan. While conflict and violence are widely explored issues in the scholarship dealing with Arabic literature, the same is not true for dialogue and peaceful coexistence. Despite their growing popularity, Peace studies have not broken through the wall of Arabic literary studies yet. The cliché can be challenged by changing our perspective and highlighting the role of literature as a bridge between different faiths and communities. Moreover, we need to re-think the relation between literature and peace not as a secondary corollary of the more familiar literature/war pattern, but as a study subject in its own right. It is necessary to point out the importance of reflecting on positive peace in modern and contemporary Arabic literature, and to start building a new critical discourse revolving around peacebuilding.